Indium-Mediated Reformatsky Reaction of Iododifluoro Ketones with Aldehydes: Preparation of α,α-Difluoro-β-hydroxyketone Derivatives in Water - Li, Zhongyuan; Huang, Jinwen; Ni, Zhuang; Sun, Ran; Nie, Hui; Tang, Hui; Song, Lixing; Wu, Fanhong (SynOpen, 2022)
Indium can efficiently mediate the Reformatsky reaction of iododifluoroacetylketones with aldehydes to afford the corresponding α,α-difluoro-β-hydroxyketones in high yield in pure water This reaction has excellent substrate suitability and functional group selectivity and provides an efficient approach for the synthesis of bioactive molecules containing the α,α-difluoro-β-hydroxyketone pharmacophore.
Keywords: Indium; Reformatsky reaction; α-iodo-α,α-diﬂuoroketone; α,α-difluoro-β-hydroxyketone